IMBANGI HEGEMONI JURNALISME MAINSTREAM MELALUI JURNALISME WARGA - Alamsyah, Feri Ferdinan (Media Bahasa, Sastra, dan Budaya Wahana, 2016)
AbstractFeri Ferdinan AlamsyahIn Indonesia, the hegemony of mainstream journalism clearly visible especially when the media broadcasting live footage events of 2014 presidential election. The media implied that the information broadcasted puts more weight to certain party. It shows as if the media taking sides by carrying certain interest. This broadcast practise in contrary to the spirit of journalism which supposed to be in serve for public interest.This study focuses on how citizen journalism can counterbalance the hegemony of mainstream journalism. Through the theory of social construction from Berger and Luckmann, citizen journalism constructed simultaneously with aspects of externalization, objectivation and internalization. That citizens or society could apply citizen journalism on the basis willing to share, which run continuously, so it becomes a habit and finally the society has certain purport against him thathave concern for the situation surrounding.Citizen journalism is an activity to collect, process and communicate information through public areas, both virtual and conventional. This activity is carried out by citizens that are laymen and amateurs to the activity.Citizen journalism can counterbalance the hegemony of mainstream journalism. He gave alter- native information to the public about an event. In addition, citizen journalism also supplements the information had not submitted the mainstream mass media, so that the information is displayed in full. Key word: citizen journalism,  hegemony